Seduced, abandoned, and reborn : visions of youth in middle-class America, 1780-1850 - Hessinger, Rodney (Early American studies., 2005)
In attempting to steer young adults safely away from the dangers of market-driven society, reformers in early America created values that came to define the emerging urban middle class.